Rtlp2 enhances thermotolerance in rice - Wen Du; Xiaohan Zhang; Jian Zhang; Yugui Wu; Xiaojun Chen; Qiuhong Chen; Dongyang Lei (Plant Stress)
The harmful effects of heat stress on agricultural production are becoming increasingly severe. Thaumatin-like proteins (TLPs) have been demonstrated to play crucial roles in regulating plant resistance to biotic and abiotic stresses. However, their involvement in plant thermotolerance is poorly understood. This study aims to investigate the major-effect gene in a key quantitative trait locus (QTL) associated with rice thermotolerance, namely Rtlp2, which encodes a rice TLP. The Rtlp2 protein was found to be localized in the endoplasmic reticulum (ER). Rice seedlings overexpressing the Rtlp2 gene showed significantly enhanced thermotolerance compared to the wild type, while rtlp2 mutant exhibited increased susceptibility to heat stress. After 48 h of heat stress treatment, rice plants overexpressing Rtlp2 exhibited reduced accumulation of hydrogen peroxide (H2O2) and cell death compared to the wild-type. Conversely, the mutant plants showed the opposite behavior. The results of gene expression level analyses revealed that Rtlp2 positively regulates rice thermotolerance through the modulation of rice heat shock transcription factors (HSFs) and heat shock proteins (HSPs) network. After undergoing natural heat stress in the field, the rice lines overexpressing Rtlp2 showed higher seed setting rate and yield per plant compared to the wild-type. In addition, Rtlp2 has also been found to positively regulate grain length and grain weight in rice. This study provides valuable resources for addressing the challenge of increasing environmental heat and promoting the breeding of heat-tolerant rice varieties.